Identification Of Circular Economy Criteria and Indicators in International Standards to Support Global Sustainability: A Systematic Literature Review - Anwardi Anwardi; Ahmad S. Indrapriyatna; Jonrinaldi Jonrinaldi; Dody Ichwana Putra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The transition to a circular economy (CE) is critical for achieving global sustainability goals. However, the identification and integration of standardized criteria and indicators to support CE remain a challenge. This study conducts a systematic literature review (SLR) to identify the criteria and indicators embedded in international standards and their implications for CE implementation. Using the PRISMA methodology, 100 relevant publications were analyzed, focusing on prominent standards such as ISO, the EU Circular Economy Action Plan, the Ellen MacArthur Foundation framework, Cradle to Cradle, and GRI. The findings reveal recurring criteria, including resource efficiency, waste reduction, sustainable product design, and compliance with environmental regulations. Indicators such as carbon footprint, recycling rates, and material reuse emerge as pivotal for assessing CE progress. These findings offer valuable insights for policymakers and organizations in developing comprehensive strategies to advance CE adoption. Recommendations include the harmonization of standards, enhanced stakeholder collaboration, and the integration of CE principles across sectors. Keywords: Circular Economy, International Standards, Global Sustainability